Common Errors of Reliability and Validity Testing in Guidance and Counselling Research - Azzahrah, Humairah; Ahman, Ahman; Fauzi, Irfan; Hafiyani, Silmi; Agustina, Silvia (CV. Creative Tugu Pena, 2023)
This research aims to identify common problems that occur in reliability and validity testing in research in the field of guidance and counselling. This research uses the Systematic Literature Review (SLR) method, which examines and reviews several articles related to common errors in reliability and validity testing. This research searched for several articles from various sources such as Google Scholar, Semantic Scholar, Springer, Routledge Taylor & Francis Group, Research Gate, and frontiersin.org within the past 5 years (2013-2023). The articles that have been searched are then analysed for common errors that appear related to reliability and validity testing, the results of this analysis are presented in tabular form and explained descriptively. The results of this study indicate that several studies in the field of counselling have 9 common errors that are often made in conducting quantitative research. These errors are: not including reliability and validity, not iterating and revising unreliable items, not conducting content validity analysis, not conducting construct validity analysis, mismatching the instrument with the characteristics of the item, the absence of judgment validity, not describing favourable and unfavourable items, limited samples on the instrument, and doubtful construct validity and the need for reliability testing on a wide scale. His research can be a study and reference material in conducting quantitative research, especially in the field of guidance and counselling. Keywords: Common Errors, Reliability and Validity, Guidance and Counseling